The Implementation of Anti-Fraud Strategy to Achieve Good Corporate Governance - Astrini Aning Widoretno; Agustinus Nicholas Tobing (Future Science, 2021)
Any type, scale, or shape of organization has risks of fraud. That required an anti-fraud strategy to detect and prevent the occurrence of fraud. The internal audit mostly takes an important role in the implementation of the anti-fraud strategy. This paper aims to analyze the role of internal audit in the implementation of the anti-fraud strategy and the implementation of the anti-fraud strategy of PT.XYZ. This study used a qualitative approach with field study data collection techniques. This research uses 4 anti-fraud strategies that are whistle blowing system, a code of conduct, fraud training for employees and fraud risk assessment to analyze the implementation of anti-fraud strategy of PT.XYZ. The results of this study indicate that internal audit plays an active role in applying anti-fraud strategy and generally anti-fraud strategy of PT.XYZ has met the aspects of detection, prevention, and investigation.